2022
DOI: 10.1017/s0305741022000145
|View full text |Cite
|
Sign up to set email alerts
|

Producing Scientific Motherhood: State-led Neoliberal Modernization and Nannies' Subjectivity in Contemporary China

Abstract: This paper uses the perspective of “state-led neoliberal modernization” to explore the collusion of the state and the market in the construction of scientific motherhood and its effect on rural nannies in China. It claims that the state and the market work together to shape rural nannies’ modern subjectivity in the neoliberal economy through the commercial training programme of scientific motherhood. Based on a case study in Shanghai, this paper argues that the training for scientific motherhood attempts to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Furthermore, workers’ subjective perception of their care work plays a more important role in their mental health. This result is consistent with the previous finding that home care workers might have a positive experience of their work because they find social meaning in their care work [ 14 ]. However, working environment is not associated with workers’ depression levels, which is different from the previous results found regarding caregivers in other countries [ 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Furthermore, workers’ subjective perception of their care work plays a more important role in their mental health. This result is consistent with the previous finding that home care workers might have a positive experience of their work because they find social meaning in their care work [ 14 ]. However, working environment is not associated with workers’ depression levels, which is different from the previous results found regarding caregivers in other countries [ 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…A large-scale random-sample survey of domestic workers conducted in 2019 revealed that only 1.6% of care workers in Beijing have labor contracts [ 10 , 11 ]. Other studies show that these female rural migrant care workers usually work overtime, lack leisure time, and sometimes have to face abuse from clients [ 12 , 13 , 14 , 15 , 16 , 17 ]. Although scholars have paid attention to these female rural migrant care workers’ working conditions and relationships with their clients, the mental health of these workers has not received attention from scholars.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations